Amacrine cell interactions underlying the response to change in the tiger salamander retina - Maguire, G (J Neurosci, 1989)
The neural circuitry and pharmacology underlying transient signal formation at the bipolar-amacrine cell interface were studied. Synaptic currents were measured with whole cell patch clamp in retinal slices. Cell types were identified with Lucifer yellow staining. Activity was initiated with puffs of kainate of known time course and spatial spread delivered at bipolar dendrites. OFF bipolar cells responded to kainate with a sustained inward current, but ON bipolar cells were silent. Two types of amacrine cell were found: (1) narrow field cells, with processes that extended laterally less than 200 microns, responding with a sustained inward current, and (2) wide field cells, with processes that extended laterally by up to 1 mm, responding with a brief transient inward current followed by a more sustained outward current. We pharmacologically dissected the synaptic interactions underlying the transient current in the wide field amacrine cell. In the presence of 5-aminovaleric acid (AVA), the time course of this transient current was increased so that it resembled the response of bipolar cells. Because AVA is a GABAB antagonist, it appears to block an opposing signal that truncates the sustained excitatory bipolar input, thereby generating the transient. GABAB specificity is confirmed by (1) block of the transient inward current by baclofen, a GABAB agonist, and (2) block of the baclofen effect by AVA. The site of GABAB action appears to be presynaptic to the amacrine cell membrane because neither baclofen nor AVA, in combination with picrotoxin, had a direct effect at the amacrine cell membrane. GABAB receptors are often found at presynaptic terminals where they modulate calcium or potassium conductances. It has been shown that bipolar cell terminals receive a GABAergic synaptic input (Vaughn et al., 1981; Wu et al., 1981; Tachibana and Kaneko, 1987). The narrow field sustained-responding amacrine cells appear to be GABAergic (Werblin et al., 1988). This suggests that transient activity measured in wide field amacrine cells is formed at a population of bipolar cell terminals by GABAergic feedback from narrow field amacrine cells at GABAB receptors.